Educação musical em ambiente virtual: desafios de implementação e possibilidades do Centro de Música SESC - Locateli, André Luis (2023)
This research is part of the New Technologies in Education Research line of the Graduate Program in Education: Curriculum at PUC São Paulo. It aims to analyze the perception of music educators at Sesc Music Center who taught musical instrument courses supported by a distance environment via the internet. As a methodology, qualitative research was carried out with the application of a questionnaire for the educators of the Centro Experimental de Música do Sesc. distance can be used as an option for teaching music, especially if combined with other face-to-face modalities and if used in a planned and strategic way